Pesticide safety training to promote sustainable practices among French tree fruit and fresh vegetable farmers: A pre-post intervention survey - Sonia Grimbuhler; Jean-François Viel (PLoS ONE, 2025)
Objective Reducing pesticide exposure in agricultural activities remains a major challenge, particularly for crops that rely heavily on pesticides, such as fruits and vegetables. Integrated pest management technology requires a strong safety culture to effectively reduce pesticide use. The aim of this study is to assess the impact of mandatory safety training on the knowledge and perceptions of pesticide use among French fruit and vegetable farmers and farm workers. Methods Farmers throughout France were approached during mandatory training for pesticide-related activities. Trainees were asked to complete a self-administered questionnaire that included demographic and occupational data as well as a safety climate scale specifically designed for the agricultural sector. A total of 182 farm managers or workers involved in fruit cultivation and 164 involved in vegetable cultivation completed the questionnaire at the beginning and end of the session, enabling us to compare pre- and post-training scores using a multiple measures design. Statistical analyses were conducted using paired t-tests and mixed models for repeated measures. Results We noted increases in global safety climate scores (8.2% and 8.6% among fruit and vegetable producers, respectively; p < 0.001) and each of their seven dimension scores after trainees completed the course. The largest increases among fruit producers were observed in the communication and feedback, and the knowledge dimensions (16.6% and 8.6%, respectively; p < 0.001). Among vegetable producers the greatest improvements were found in the communication and feedback, and the teamwork climate dimensions (14.9% and 9.4%, respectively; p < 0.001). Score improvements remained highly significant in multivariate analyses, as few covariate-by-time interactions were found. Conclusions This study demonstrates that pesticide training significantly enhances the safety climate perception among French fruit and vegetable producers. The long-term effects of this intervention should be evaluated, with the ultimate goal of reducing risks to human health and the environment.